Clonagem e estudos de expressão de enzimas do fungo filamentoso Trichoderma harzianum IOC-3844 envolvidas na degradação de biomassa - Malagó Junior, Wilson (Universidade Federal de São Carlos, 2012)
The plant biomass is a large-scale available resource and one of its more important applications is the second-generation ethanol production. However, the enzyme cost is one of the biggest barriers for economically viable ethanol from biomass. Therefore, it is important to identify fungal strains that can produce high concentrations of plant biomass-degrading enzymes. The aim of this work was to clone, study the gene expression and characterize the plant biomass-degrading transcript set of the filamentous fungus Trichoderma harzianum IOC-3844. A total of 1,543 highquality reads from the Trichoderma harzianum IOC-3844 cellulose induced cDNA library were organized into 1,002 transcripts representing 167 contigs and 835 singlets. Of these 1,002 transcripts 646 had unknown functions and 356 showed associated functions. Among the transcripts with associated functions, we found 20 transcripts related to plant biomass deconstruction. The real time PCR analysis of Trichoderma harzianum IOC-3844 mycelia grown for 36 and 60 hours in cellulose, revealed that the levels of the following mRNAs were induced by at least 2,000-fold when compared to uninduced mycelia: cbh1, cbh2, egl1, egl2, egl3, egl7 and swo1. In some cases, the values were higher than 100,000-fold. Among the transcripts analyzed by real time PCR, cbh1, cbh2 and egl7 exhibited the highest expression levels. The Trichoderma harzianum IOC-3844 exhibited a repertoire with high expression of plant biomassdegrading transcripts. The enzymes EGIII and Xyn2 were recombinantly expressed in Pichia pastoris, showing good quality purification and good enzymatic activity. The heterologous expression assays made possible future studies aiming at the industrial application of the enzymes. Therefore, this strain showed potencial to produce biomassdegrading enzymes for second-generation ethanol production and to be a source of enzymes for the paper industry
Keywords: Fungos; Trichoderma harzianum; Celulase; Hemicelulase; Transcriptoma; Expressão heteróloga; Biblioteca de cDNA; Etanol de segunda geração; Biomassa; Trichoderma harzianum; Transcriptome; Cellulases; Hemicellulases; Xylanases; Biomass; cDNA library; Second-generation ethanol; Heterologous expression; CIENCIAS BIOLOGICAS::GENETICA